SYSTEM OF TRAINING SPECIALISTS IN THE SPHERE OF DOCUMENT SUPPORT OF MANAGEMENT (FROM THE EXPERIENCE OF THE DEPARTMENT) - DANYLYUK, Serhiy; TKACHENKO, Vadym; ZANORA, Volodymyr (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2020)
The article reveals the specific features of the system of training specialists in the field of document support of management (DSM). Attention is focused on the list of documents in which the internal activities of the organization are recorded. They include: 1) organizational-and-legal documents; 2) administrative documents; 3) information-and-reference documents. The content of the curriculum in the discipline "Document Support of Management" is also disclosed, which includes the following sections: 1) the purpose of the course, sources and literature; 2) documentation of management activities; 3) organization of work with documents. Attention is focused on the DSM service and its role in the organization of information-and-document management; the concept of "document flow", organization and stages of document circulation; organization of work with citizens’ appeals; organization of documentation with the help of information technologies. Students get acquainted with the preparation and execution of official documents, registration forms, deadlines. Particular attention is paid to the systematization and storage of documents, the compilation of nomenclatures of cases, the functions of archival departments, the principles and criteria of examination of the value of documents, the organization of expert commi-?sions. practical issues of formation and registration of cases, compilation of descriptions of cases, acts, the order of accounting of archival documents and preparation of certificates of social-and-legal nature at the request of citizens are also considered. Practice in the organization and technology of DSM gives students the opportunity not only to consolidate theoretical knowledge, but also to master the professional skills of a specialist in organizing all stages of working with documents from receipt to archival storage in a particular institution. It is noted that the adoption of an effective management decision significantly affects the efficiency and quality of management, contributes to achieving this goal. Modern technologies allow you to successfully solve the problem of effective work with a huge number of documents (including reception, registration, performance monitoring, information analysis, creation of information retrieval systems).